IMPLEMENTASI PERATURAN BUPATI SEKADAU NOMOR 9 TAHUN 2012 DI KANTOR PELAYANAN PERIJINAN TERPADU KABUPATEN SEKADAU - Welli Center E.42009068 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
The title of this essay concerns raised by the application of operational standards and procedures in the Office of Licensing Services Integrated(KPPT) Sekadau is still not optimal accordance with decree No. 9 of 2012. It is seen from the licensing of turnaround time can not be completed on time. This research uses descriptive qualitative research model. Research sites in the District Integrated Licensing Service Office Sekadau. The research subject is KPPT Head Office, officer in KPPT and the society that have filed in the Office of Licensing Services licensing Integrated Sekadau District. While the object of this research is the implementation of the decree No. 9 of 2012 Sekadau itself. The conclusion of this study is, the application of operational standards and procedures adopted by the Office of Licensing Services Integrated Sekadau District as set out in the decree Sekadau No. 9 in 2012 has not been optimal. Communication and implementing disposition made ??by KPPT Sekadau been good but resources Integrated Licensing Service Office which is still inadequate and bureaucratic structures are long and convoluted to be the cause of not optimal implementation of the policy. For the given input is to add existing resources to be able to support the optimization of the application of operational standards and procedures, and can cut through the red tape as possible.Keywords: Implementation of the Integrated Licensing Services